Infective Juveniles of the Entomopathogenic Nematode Steinernema scapterisci Are Preferentially Activated by Cricket Tissue - Lu, Dihong; Sepulveda, Claudia; Dillman, Adler R. (PLOS ONE, 2017)
Entomopathogenic nematodes are a subgroup of insect-parasitic nematodes that are used in biological control as alternatives or supplements to chemical pesticides. Steinernema scapterisci is an unusual member of the entomopathogenic nematode guild for many reasons including that it is promiscuous in its association with bacteria, it can reproduce in the absence of its described bacterial symbiont, and it is known to have a narrow host range. It is a powerful comparative model within the species and could be used to elucidate parasite specialization. Here we describe a new method of efficiently producing large numbers of S. scapterisci infective juveniles (IJs) in house crickets and for quantifying parasitic activation of the IJs upon exposure to host tissue using morphological features. We found that parasite activation is a temporal process with more IJs activating over time. Furthermore, we found that activated IJs secrete a complex mixture of proteins and that S. scapterisci IJs preferentially activate upon exposure to cricket tissue, reaffirming the description of S. scapterisci as a cricket specialist.